Two-stage sort planning for express parcel delivery. (2nd December 2021) - Khir, Reem; Erera, Alan; Toriello, Alejandro
Abstract: The design and control of effective sortation systems has become more complex as both the volume of parcels and also the number of time-definite service options offered by parcel carriers have grown. In this article, we describe approaches for planning two-stage parcel sort operations that explicitly consider time deadlines and sorting capacities. In two-stage sorting, parcels are sorted into groups by a primary sorter and then parcels from these groups are dispatched to secondary stations for final sort. We define a sort planning optimization problem in this setting using mixed-integer programming, where the primary objective is to minimize operational cost subject to machine capacity and parcel deadline constraints. Since a detailed optimization problem for sort planning based on flows in a time–space network is difficult to solve for realistically-sized instances, we develop an alternative formulation that is easier to solve and shares the same feasible region of first-stage sorting decisions with the detailed model; for many practical objective functions, this simpler model can be used to find cost-optimal solutions to the detailed model. We illustrate the proposed modeling approach and its effectiveness using real-world instances obtained from a large parcel express service provider.